2004
DOI: 10.1007/s00406-004-0542-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of research findings on the efficacy of interpersonal therapy for depressive disorders

Abstract: The efficacy of IPT proved to be superior to placebo, similar to medication and did not increase when combined with medication. Overall, IPT was more efficacious than CBT. Current evidence indicates that IPT is an efficacious psychotherapy for DSD and may be superior to some other manualized psychotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(143 citation statements)
references
References 40 publications
4
129
0
10
Order By: Relevance
“…Par ailleurs, aucune différence statistiquement significative n'a été décelée entre la thérapie interpersonnelle (TIP) et les antidépresseurs (De Mello, et al, 2005) (NICE, 2009). Les résultats sont toutefois moins unanimes en ce qui concerne la thérapie psychodynamique (TPD).…”
Section: Pour Les Troubles Dépressifsunclassified
“…Par ailleurs, aucune différence statistiquement significative n'a été décelée entre la thérapie interpersonnelle (TIP) et les antidépresseurs (De Mello, et al, 2005) (NICE, 2009). Les résultats sont toutefois moins unanimes en ce qui concerne la thérapie psychodynamique (TPD).…”
Section: Pour Les Troubles Dépressifsunclassified
“…Interpersonal psychotherapy (IPT) is a focused, short-term therapy originally developed for depression, which emphasises its interpersonal context (Klerman & Weissman, 1993) IPT has been shown to be effective for major depressive episode at any stage in life (de Mello, de Jesus Mari, Bacaltchuk, Verdeli, & Neugebauer, 2005). It has proven effective for PND in controlled trials with large sample sizes, different comparison groups, and individual and group settings (Grote et al, 2009;O'Hara, et al, 2000;Miniati et al, 2014;Spinelli, & Endicott, 2003).…”
Section: Interpersonal Therapy Is a Relationship-focussed Pnd Treatmentmentioning
confidence: 99%
“…In a large RCT, Elkin et al (1989) found that IPT is equally effective to medication and CBT, with some evidence for increased efficacy of IPT for severely depressed patients. There is also preliminary evidence suggesting the superiority of IPT over alternative psychotherapies (Cuijpers et al 2008(Cuijpers et al , 2011, specifically supportive counselling (Barth et al 2013) and CBT (de Mello et al 2005).…”
Section: Interpersonal Therapy (Ipt)mentioning
confidence: 99%